Lack of a p16INK4a/ARF locus in fish genome may underlie senescence resistance in the fish cell line, EPC. (August 2022) - Futami, Kunihiko; Sato, Shunichi; Maita, Masashi; Katagiri, Takayuki
Abstract: Unlike most mammalian cell lines, fish cell lines are immortal and resistant to cellular senescence. Elevated expression of H-Ras contributes to the induction of senescence in a fish cell line, EPC, but is not sufficient to induce full senescence. Here, we focused on the absence of a p16 INK4a /ARF locus in the fish genome, and investigated whether this might be a critical determinant of the resistance of EPC cells to full senescence. We found that transfected EPC cells constitutively overexpressing p16 INK4a exhibited large size and flat morphology characteristic of prematurely senescent cells; the cells also showed p53-independent senescence-like growth arrest and senescence-associated β-galactosidase (SA-β-gal) activity. Furthermore, the mRNA levels of proinflammatory senescence-associated secretory phenotype (SASP) factors increased in EPC cells constitutively overexpressing p16 INK4a . These results suggest that the lack of p16 INK4a in the fish genome may be a critical determinant of senescence resistance in fish cell lines. Highlights: p16 INK4a induces full senescence in EPC cells in a p53-independent manner. p16 INK4a induces proinflammatory SASP factors in EPC cells. Neither ARF nor Cdkn2ab contributes to premature senescence in EPC cells. Lack of p16 INK4a may be a determinant of senescence resistance in EPC cells.